The Effect of Intrinsic Motivation and Work Engagement on Work Productivity of Employees at the Department of Education of Mamuju Regency - Silvia Silvia; Suwanti Suwanti; Adam Ramadhan; Muh. Rezky Naim; J. Fuji Inzani SL (Economics and Digital Business Review, 2026)
This research was undertaken to examine how intrinsic motivation and work engagement, both separately and jointly, shape the work productivity of employees at the Department of Education of Mamuju Regency. Employee productivity in public sector organizations remains a fundamental concern within the agenda of bureaucratic reform, particularly in regional agencies that are expected to deliver educational services that are prompt, accurate, and accountable. Adopting a quantitative associative research design executed through a survey, the study treated the entire body of civil servants serving at the agency, numbering sixty-nine persons, as its target population, and enrolled all of them as respondents by means of a total sampling or census technique, thereby eliminating sampling error altogether. Primary information was gathered through a questionnaire comprising eighteen statement items scored on a five-point Likert scale, and was supplemented by non-participant observation, library research, and documentary review. The material so obtained was subsequently processed through Pearson Product Moment validity testing, Cronbach's Alpha reliability testing, multiple linear regression, partial (t) testing, simultaneous (F) testing, and the coefficient of determination, with the aid of IBM SPSS Statistics version 23. The analysis reveals that intrinsic motivation exerts a positive and statistically significant partial influence upon work productivity (b = 0.428; t = 4.250; sig. 0.000), while work engagement likewise produces a positive and significant partial influence (b = 0.353; t = 3.148; sig. 0.002). Taken together, the two variables significantly determine work productivity (F = 18.031 > 3.136; sig. 0.000), accounting for 35.3 percent of its variation, with the residual 64.7 percent attributable to determinants lying beyond the model. Judged by standardized beta coefficients, intrinsic motivation (0.432) emerges as the more dominant predictor relative to work engagement (0.320). These results imply that efforts to strengthen productivity within the public sector are more effectively initiated through the satisfaction of employees' basic psychological needs, and most particularly the need for competence, which this study identifies as the weakest indicator in the entire measurement model.